CREATING ENGAGING E-MODULES FOR TEACHING PROCEDURE TEXT WRITING TO SEVENTH GRADERS AT ISLAMIC INTEGRATED JHS HARAPAN MULIA PALEMBANG USING GOOGLE SITES - Sumiati, Sumiati; Indrawati, Sri; Ernalida, Ernalida (University of Kuningan, 2023)
Abstract:The development of current e-module for writing procedural text with Google stie was done and applied for seventh graders of Integrated Islamic JHS Harapan Media Palembang This R&D applied the development model of Dick, Carey, and Carey to produce a valid, practical, and effective e-module of writing procedure text with Google Site. From the text, the learners and the teachers required creative and innovative e-module for writing procedure text with Google Site to develop learners’ learning independence, interest, and motivation. The research subjects were the 93-seventh graders and 3 Indonesian language teachers of Integrated Islamic JHS Harapan Mulia Palembang taken by saturated sampling. On the other hand, the effectiveness test involved 24 learners from different class within the same grade. The applied sampling technique was saturated sampling technique. The validity test of the e-module with Google site involved three experts. They were material, language, and media experts. The validity with material expert obtained a mean of 4.75, categorized as valid. The validity with language experts obtained a mean of 4.33, categorized as extremely valid. Then, the validity test with the media expert obtained a mean score of 4.92, categorized as very valid. The practicality test of the e-module with Google site was based on the one-to-one, small group, and field tests.The one-to-one test obtained a mean of 4.15, categorized as practical. The small group test obtained a mean of 4.21, categorized as very practical. Then, the field test obtained a mean of 4.14, categorized as practical. The effectiveness test of the e-module for writing procedure text with google sites was based on the pretest-posttest results. The pretest result obtained a mean score of 54.95, categorized unaccomplished while the posttest obtained the results of 81.21, categorized accomplished. From the development of an e-module for writing procedure text with Google site, the result showed that the seventh graders of Integrated Islamic JHS Harapan Mulia Palembang found the developed module valid and practical to learn procedure text writing. The product was also effective to improve the learners' procedure text writing.